Lipoaspirate-derived adult mesenchymal stem cells improve functional outcome during intracerebral hemorrhage by proliferation of endogenous progenitor cells: Stem cells in intracerebral hemorrhages - Fatar, Marc; Stroick, Mark Gregor; Griebe, Martin; Marwedel, Irma; Kern, Susanne; Bieback, Karen; Giesel, Frederik L.; Zechmann, Christian; Kreisel, Stefan H.; Vollmar, Frederike; Alonso, Angelika; Back, Walter; et al. (Neuroscience letters, 2008)
Stem cell therapy seems promising in reducing deficits after focal cerebral ischemia. As stroke may result from intracerebral hemorrhage (ICH) in up to 20% we investigated whether human processed lipoaspirate mesenchymal stem cells (PLA-MSC) influence the functional outcome, migration behavior and the activation of endogenous progenitor cells. Experimental ICH was induced by stereotactic administration of collagenase in rats randomly assigned to the control or treatment group. The latter received 3×106 PLA-MSC by intravenous (i.v.) injection 24h after ICH induction. The outcome was continuously monitored using the RotaRod test over a period of 4 weeks. Morphometric analysis of ICH was performed consecutively by magnetic resonance imaging (MRI) studies and immunohistochemical analysis. The RotaRod test revealed a significant 1.5-fold improvement (p<0.005) in functional outcome for the PLA-MSC treated group after 4 weeks compared to controls. Histological and MRI assessment of lesion size showed no difference between the two groups. Although i.v. injected human cells could not be detected in the post mortem brain, evaluation of the number of endogenous progenitor cells revealed a twofold increase in the treated animals compared to controls. Treatment with PLA-MSC improved the functional outcome significantly in an experimental ICH model. This effect was achieved by stimulation of endogenous progenitor cells rather than integration and differentiation of the infused PLA-MSC.
Gesehen am 24.03.2021